2019
DOI: 10.3390/socsci8120326
|View full text |Cite
|
Sign up to set email alerts
|

Connecting through Technology: Smartphone Users’ Social Cognitive and Emotional Motivations

Abstract: Smartphones provide various services not only for social purposes but also for personal desires. This study aims to understand the multi-dimensional motivations of smartphone users. An extended motivational framework was developed using perceived benefits (i.e., expected benefits) and social influence (i.e., social identity achieved from mobile social media) from a social cognitive perspective, which was then expanded to incorporate the second-order construct of emotional attachment (i.e., emotional desires). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 73 publications
(98 reference statements)
0
15
0
Order By: Relevance
“…Zhang & Mao, 2012). Mäntymäki and Salo (2015) found that functional value was significant in influencing teenagers’ purchase intentions for virtual goods, and Youn (2016) reasoned the influential role of functional (or utilitarian) value in smartphone usage. However, not all prior studies have shown consistent findings.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang & Mao, 2012). Mäntymäki and Salo (2015) found that functional value was significant in influencing teenagers’ purchase intentions for virtual goods, and Youn (2016) reasoned the influential role of functional (or utilitarian) value in smartphone usage. However, not all prior studies have shown consistent findings.…”
Section: Methodsmentioning
confidence: 99%
“…Several prior studies have concluded that social value plays a significant role in influencing the consumer behavior (K. Yang & Jolly, 2009), such as the purchasing behavior of virtual goods in a social virtual world (Mäntymäki & Salo, 2015) and social networking communities (H.-W. Kim, Gupta, & Koh, 2011), smartphone usage (Youn, 2016), and usage-related decision-making in regard to mobile apps (Zolkepli, 2016). Due to this, it is likely that social value derived from LINE use has the significant positive association with the continuation intentions toward its use. Hypothesis 1: Social value has the direct positive association with continuation intentions toward LINE use. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most interestingly, this research reveals that consumers' smartphone attachment encompasses strong positive (i.e., passion) and negative (i.e., distress) as well as cognitive (e.g., perceived safe haven) and emotional (e.g., passion) elements. Prior research on attachment has referred to one specific perspective and thus provided an incomplete picture (Holte & Ferraro, 2021; Youn, 2019) while only recommending the integration of different facets to gain a broad understanding of consumer attachment (Berlo et al., 2020). Because some of the facets have been used to describe attachment to humans (Bowlby, 1977), the findings of this study imply that consumers have a similar attachment to their smartphone as to humans, supporting existing findings on smartphone attachment (Konok et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Research on information systems predominantly refers to separation distress (Cheever et al., 2014; Han et al., 2017; Hartanto & Yang, 2016; Nie et al., 2020) as one of the central functions of the attachment system (Ainsworth et al., 1978; Hazan & Shaver, 1994). However, the other facets—namely, proximity maintenance (i.e., perceived need to be near the smartphone), safe haven (i.e., desire to return to the smartphone for safety and comfort), secure base (i.e., the perceived security the smartphone provides)—have received less attention (Youn, 2019). To gain a comprehensive understanding of attachment to smartphones, the literature on human attachment recommends considering all four facets (Huang et al., 2020).…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%